Hypothalamic plasticity in response to changes in photoperiod and food quality: An adaptation to support pre‐migratory fattening in songbirds?. (22nd October 2020) - Majumdar, Gaurav; Yadav, Garima; Malik, Shalie; Rani, Sangeeta; Balthazart, Jacques; Kumar, Vinod
Abstract: In latitudinal avian migrants, increasing photoperiods induce fat deposition and body mass increase, and subsequent night‐time migratory restlessness in captive birds, but the underlying mechanisms remain poorly understood. We hypothesized that an enhanced hypothalamic neuronal plasticity was associated with the photostimulated spring migration phenotype. We tested this idea in adult migratory red‐headed buntings ( Emberiza bruniceps ), as compared with resident Indian weaverbirds ( Ploceus philippinus ). Birds were exposed to a stimulatory long photoperiod (14L:10D, LP), while controls were kept on a short photoperiod (10L:14D, SP). Under both photoperiods, one half of birds also received a high calorie, protein‐ and fat‐rich diet (SP‐R, LP‐R) while the other half stayed on the normal diet (SP‐N, LP‐N). Thirty days later, as expected, the LP had induced multiple changes in the behaviour and physiology in migratory buntings. Photostimulated buntings also developed a preference for the rich food diet. Most interestingly, the LP and the rich diet, both separately and in association, increased neurogenesis in the mediobasal hypothalamus (MBH), as measured by an increased number of cells immunoreactive for doublecortin (DCX), a marker of recently born neurons, in buntings, but not weaverbirds. This neurogenesis was associated with an increased density of fibres immunoreactive for the orexigenic neuropeptide Y (NPY). This hypothalamic plasticity observed in a migratory, but not in a non‐migratory, species in response to photoperiod and food quality might represent an adaptation to the pre‐migratory fattening, as required to support the extensive energy expenses that incur during the migratory flight. Abstract : This study tested the idea that enhanced hypothalamic neuronal plasticity is associated with the vernal migration by exposing migratory buntings and non‐migratory weaverbirds to winter‐ and summer‐like photoperiods and normal and rich diets. Buntings, not weaverbirds, showed a preference for a rich diet and, in response to long photoperiod, they exhibited body fattening and extensive mediobasal hypothalamic neurogenesis, representing an adaptation to the pre‐migratory fattening in migrants.